Study on Rock Burst Early Warning in the Working Face of Deep Coal Mines Based on the Law of Gas Emission - Qinghua Zhang; Shudong He (Advances in Civil Engineering)
This study is aimed at predicting rock burst disasters in high gas mines. First, the distribution law and correlation of gas and stress in the F15-17-11111 working face of Pingdingshan No. 13 Mine were analyzed based on the coupling relationship between gas emission and stress in the working face. Next, the relationship between gas emission and stress distribution was revealed, and an early warning method of rock burst in the deep mine working face based on the law of gas emission was proposed and applied to the F15-17-11111 working face. Finally, the critical value of the gas concentration indicator for rock burst early warning in the F15-17-11111 working face was determined as 0.05%. The following research results were obtained. The gas emission and the mining stress in the F15-17-11111 working face are negatively correlated. Mechanically, their correlation satisfies the typical coupling. Besides, the critical value of the gas concentration indicator determined by the proposed early warning method boasts high accuracy in predicting rock burst disasters. It can be used as an early warning method for underground rock burst disasters to promote the safety of working face mining. The research results provide reference and guidance for the monitoring and early warning of rock burst disasters in deep high gas mines.